Length-weight relationship of Sufflamen fraenatus (Latreille, 1804) and Zenodon niger (Ruppell, 1835) - Sahayak, Satish (Indian Journal of Fisheries, 2011)
The relationship between total length and total weight in balistids is not significantly different in males and females. The common equation for both the sexes in Sufflamen fraenatus is Log W= -9.0429+2.7296 log L or W=0.000000000905* L 2.7296, R2 = 0.9301, and in Zenodon niger is Log W= -6.507+2.085 log L or W=0.0000003117* L2.08556 R2 = 0.6749.